Dismantling of a breakthrough: the Kyoto Protocol - just symbolic policy! - Christoph Böhringer; Carsten Vogt (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
We show that U.S. withdrawal from the Kyoto Protocol is straightforward under political economy considerations. The reason is that U.S. compliance costs exceed low willingness to pay for dealing with global warming in the U.S. The withdrawal had a crucial impact on the concretion of the Protocol prior to its likely ratification at the end of 2002. Remaining non-EU Parties to the Kyoto Protocol gained veto bargaining power and, thus, were successful in asserting far reaching concessions from the EU on sink credits and tradability of emission rights. Taking these concessions into account, the Kyoto Protocol was essentially reduced to a symbolic treaty that codifies more or less business-as-usual emissions and makes compliance a rather cheap deal.
Keywords: Q43; D58; H40; 330; climate policy; political economy; willingness to pay; Klimaschutz; Umweltabkommen; Public Choice; Willingness to pay; Welt; Vereinigte Staaten; Klimaschutz